Phytochemical screening, phenolic and flavonoid contents, antioxidant and cytotoxic activities of Graptophyllum pictum (L.) Griff - Nadechanok Jiangseubchatveera (2018)
© 2017, Chiang Mai University. All rights reserved. The phytochemical screening of the leaves of Graptophyllum pictum (L.) Griff. was carried out using the standard procedures which revealed the presence of flavonoids, steroids, tannins, coumarins, saponins, anthraquinones, phenolics and sugars. In vitro antioxidant activity, total phenolic and total flavonoid contents of four different fractions from the ethanolic leave extract of G. pictum (L.) Griff. were determined using spectrophotometric methods. The ethyl acetate fraction showed the highest total phenolic content (102.57 ± 0.19 mg gallic acid equivalent/g) and the hexane fraction contained the highest flavonoid (28.21 ± 0.04 mg quercetin equivalent/g). The ethyl acetate fraction also exhibited the highest antioxidant capacities in the DPPH radical scavenging assay with the IC50value of 0.78 ± 0.01 mg/mL and was found 69.19 ± 0.73 mg trolox equivalent capacity/g and 48.04 ± 0.49 mg ascorbic acid equivalent capacity/g when investigating by the ABTS radical scavenging assay. Moreover, the hexane, the ethyl acetate and the aqueous fractions exhibited significant cytotoxicity against MCF-7 cell lines with IC50values of 38.66, 26.01 and 20.41 μg/mL, respectively. All fractions were non-cytotoxic against Vero cells. The results of all experiments suggest that the leaves of G. pictum (L.) Griff. can be a natural candidate for rich source of antioxidants for further chemical investigation.